PLS-Based Multi-Group analysis for knowledge management in the life insurance industry - Huang, L.; Quaddus, Mohammed; Rowe, Anna; Lai, C. (IEEE, 2017)
© 2017 IEEE. Organizations implement KM with the assumption that KM will enhance organizational competitive advantages. However, little research has been conducted on their relationships in the life insurance industry which involves knowledge-intensive activities. Therefore, this paper aims to examine the antecedents of KM adoption, employees' perceptions on KM, their effects of KM practice and the impact of KM practice on organizational performance. A research model was first proposed combining the literature and results from a qualitative field study. We then developed a questionnaire based on the model and conducted an empirical pilot study to revise the research instrument. Finally, the main survey was conducted in the life insurance industry in Taiwan. The main survey data were analyzed utilizing Partial Least Squares (PLS) and PLS-based Multi-Group Analysis (MGA) techniques.